THE PLOT SEQUENCES OF DOYLE’S DETECTIVE FICTION: A DESCRIPTION OF THE CHOICE AND RELATION OF THE LEXICAL ITEMS - Laily Martin (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2011)
Plot, the ―sequence of interrelated events‖ (Foster in Pickering and Hoeper 1981:14), is a building element of literary works. This literary element assists in text reading and interpretation processes because the element shows the sequences of interrelated events that help in understanding text development. In the processes of text reading and text interpretation, plot is commonly analyzed literarily with the specific concern only to the elemental sequences of a plot. The concern to the sequences makes the plot analysis as the description of a certain construction, a text structure. Actually, plot analysis could also be conducted linguistically by analyzing certain linguistic elements and the contribution of these linguistic elements to plot description, as discussed in stylistics.The appearances of the stylistic and structural methods require two analysis types: the linguistic and the literary analyses. The stylistic method covers the linguistic analyses of the lexical items and their semantic sense relations, and the structural method covers a literary discussion on the plot sequences of the three texts. The linguistic based and literary based analyses are interrelated each other by the description of the semantic sense relations of the chosen lexical items in order to describe the sequencing of the texts‘ plot.Based on the analysis, the three Doyle‘s detective short stories are built from similar plot sequences. Each sequence is also composed from some other similar features which are arranged in a similar chronology. In summary, three plot sequences –exposition, action and climax— are built from two main features, and the other two plot sequences –resolution and conclusion— are developed by three composing features. Exposition consists of the narrative of a pre undisturbed situation and the narrative of the crime. Action consists of the deducting efforts prior to the crime scene investigation and the described actions taken during the crime scene investigation. Climax is the revelation of the tools used in the murders and the murderers themselves. Resolution shows the crime solving by mentioning the relationship of the information in the introduction, particularly the second part, and the actions taken in the Action. Conclusion ends the stories by stating punishment for the guilty murderers, the reward for the victims or the falsely accused participants and the common conclusion for public consumption. Among the five, a close similarity is seen in three plot sequences: exposition, action and resolution. Their relation is proven by the similar lexical items used in the features of the three plot sequences. The similarity causes a linkage of logics of a detective story.